Literatur Review: Edukasi Kesehatan Dalam Meningkatkan Perilaku Hidup Bersih Dan Sehat (PHBS) - M Bachtiar Safrudin; Risnawati Sari; Marlina Damayanti; Anita Pasha Dwi Wulandari; Salsabil Wulandari Saputri; Husnul Khotimah Mei Syahadati Saragih; Fadhila Zarifa Az Zahra; Nabilah Fikriyah Sarah; Nathania Zahra Hafizha; Novita Ramadhany; Sandriana Putri Faysha; Syalum Fayzayunda (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Clean and Healthy Living Behavior (PHBS) is an important effort to improve public health status through the implementation of healthy habits in daily life. However, the level of public awareness and understanding regarding PHBS is still relatively low, causing various health problems related to poor hygiene and unhealthy lifestyles. This literature review aimed to analyze the effectiveness of health education in improving Clean and Healthy Living Behavior among students and communities. The method used in this study was a literature review by analyzing scientific articles published between 2020 and 2026 from national and international journals related to health education and PHBS. The findings showed that health education had a significant positive effect on increasing knowledge, attitudes, and healthy behaviors. Various educational methods such as counseling, demonstrations, simulations, audiovisual media, interactive discussions, and digital media were proven effective in improving participants’ understanding and awareness regarding personal and environmental hygiene. In addition, continuous and interactive educational approaches were able to encourage sustainable healthy habits in schools, households, and communities. The implication of this study indicates that health education should be implemented continuously using innovative and participatory approaches to create a healthier society and improve overall quality of life.